2019
DOI: 10.1097/md.0000000000017234
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy does not improve the prognosis and lymph node metastasis rate of locally advanced cervical squamous cell carcinoma

Abstract: Locally advanced cervical carcinoma has a poor prognosis. Neoadjuvant chemotherapy (NACT) can reduce tumor size and improve tumor resection rate, but its use in large locally advanced cervical carcinoma is controversial. This study aimed to evaluate the treatment and prognosis of NACT in patients with cervical carcinoma stage IB2 or IIA2.This was a retrospective cohort study of patients who underwent type-C radical surgery and pelvic lymphadenectomy due to cervical carcinoma stage IB2/IIA2 between 2/2014 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Gupta et al (25) reported that the clinical response rate was 78.5% with TC neoadjuvant chemotherapy, while Cho et al (10) discovered 83.3% achieved clinical response with TC/TP regimen. Only 0-8.9% severe leukopenia was observed in neoadjuvant chemotherapy with TP regimen (21,26,27). The results of these studies are similar to our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Gupta et al (25) reported that the clinical response rate was 78.5% with TC neoadjuvant chemotherapy, while Cho et al (10) discovered 83.3% achieved clinical response with TC/TP regimen. Only 0-8.9% severe leukopenia was observed in neoadjuvant chemotherapy with TP regimen (21,26,27). The results of these studies are similar to our study.…”
Section: Discussionsupporting
confidence: 91%
“…A meta-analysis found that NACTS reduced the rate of adjuvant radiotherapy in LACC by reducing a high-risk factor-lymph node metastasis (7). However, there was no difference in the rate of lymph node metastasis between the NACTS group and PS group in our study, which is supported by Yan et al (21) and Hu et al (17), both of whom found that NACTS could not reduce lymph node metastasis. We found that the intermediate-risk factors--bulky tumor and LVSI(+), were significantly decreased in the NACTS group, which is consistent with other studies (10,12,17).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…grouped the patients with cervical carcinoma stage IB2 or IIA2 according to whether they received NAC or not before surgery and evaluated the treatment and prognosis of NAC [15]. The results showed that NAC did not significantly affect DFS (P = 0.453) and OS (P =0 .933) between the 2 groups.…”
Section: Acute and Late Toxicitiesmentioning
confidence: 99%
“…Therefore, it has emerged as an alternative option of treatment based on several studies that have shown a significant benefit of NAC+RS over radiotherapy alone or concurrent chemotherapy in terms of overall survival (OS) and disease free survival (DFS) [13,14]. On the other hand, some studies have reported inconsistent findings regarding the outcomes of NAC [15,16].…”
Section: Introductionmentioning
confidence: 99%